2022-VA-1435-ESGO ECO-LEAK: A Novell strategy for anastomotic leakage diagnosis in gynecologic cancer patients. (20th October 2022) - Lago, Víctor; Albert, Manel Montesinos; Segarra-vidal, Blanca; Padilla-Iserte, Pablo; Matute, Luis; Gurrea, Marta; Domingo, Santiago
Abstract : Introduction/Background: Anastomotic leakage can be checked intraoperatively with a leak test after pelvic instillation of serum followed by transrectal air insuflation, ECO-LEAK consist on viewig the presence of new free fluid in the pelvis after transrectal instilation of an enema Methodology: For a better understanding we simulated an anastomosis in an animal model one with out leak and the other with leak. The following video shows the procedure in 2 patients without leakage. the ECO-LEAK test is performed in the following sequence, after informing the patient and obtaining her consent. Results: - Gynaecological position/lithotomy Basal transvaginal ultrasound with the aim of describing the presence or absence of free fluid or other ultrasound findings (sagittal and transverse scan). At this point the stapler line can be identified as it presents a more hyperreflective aspect. - Trans anal foley catheter insertion – Filling of the balloon of the probe by direct visualization – Transvaginal ultrasound with enema: Insertion of 180cc of serum under ultrasound vision with probe in vagina and sagittal and mid-sagittal cut. – Exploration of the anastomosis in a sagittal and transversal plane. – If no new free peri-anastomotic/pelvic fluid appears, the test is considered negative. – If there is an appearance of pelvic free fluid (previously absent) or an increase in free fluid with respect to the baseline examination (fluid present at the beginning of the examination) peri anastomosis/pelvic, the test is considered positive. Conclusion: The possible theoretical advantages of this method are its rapid accessibility, ease of performance, patient comfort, reproducibility and low cost.